EFFECTIVENESS OF CONSERVATION MANAGEMENT OF OLIVE RIDLEY SEA TURTLES (LEPIDOCHELYS OLIVACEA) AT ABADI TURTLE CONSERVATION, TRISIK BEACH, KULONPROGO, YOGYAKARTA - Sri, Hidayat; Waluyo; Bidari, H. Buditami (Pusat Kajian Sumberdaya Pesisir dan Lautan IPB, 2024)
Turtles are an endangered biota around the world; one type is the Olive Ridley Turtle (Lepidochelys olivacea). Turtle extinction is caused by a decrease in the number of turtles laying eggs in their native habitat each year, hence turtle conservation is required in order to protect turtle populations. Turtle conservation in Indonesia is not yet deemed optimal; therefore, study on the effectiveness of turtle conservation, such as that of Olive Ridley Turtles at the Abadi Turtle Conservation, Trisik Beach, Kulonprogo, Yogyakarta, is required. This research was conducted in December 2022. This study uses observation, a survey, a questionnaire, and SPSS Multidimensional Scaling (MDS) to handle the data. This study has numerous components, including social, economic, ecological, environmental, legal, and institutional, as well as infrastructure dimensions. These parameters are analyzed to determine stress and sustainability values. After MDS processing, the findings showed that the ecological dimension had the minimum stress value, which is very good, at 0.42%, and the sustainability value was 99.9%. So, from an ecological standpoint, conservation is very beneficial and can be implemented to ensure the effectiveness of Olive Ridley Turtle conservation